The complex of security in the Western Balkans - Skočajič Juvan, Nina (Teorija in praksa, 2017)
After the wars came to an end following Yugoslavia's dissolution, the Western Balkans (WB) embarked upon a path of transition and reform which for various political, security, economic and other reasons is still continuing today. Based on a broader analysis of the security framework in the region, this paper identifies the main transformative processes and analyses their elements and implications, which constitute the complex security in the WB. We assess the situation at the level of individual countries and extrapolate the findings for the whole region and Europe. With a view to evaluating the region's dynamics and underlying issues that correlate with and mutually impact on each other, we divide the transformation period into three processes: stabilisation with state-building, democratisation with institution-building, and Euro-Atlantic integration. Western Balkans security has been becoming ever more complex in the past 25 years due to these unfinished processes together with unresolved past issues arising from inter-related and mutually reinforcing political, socio-economic and ethno-national elements. Moreover, new-old security challenges have emerged that are further complicating the state of security. Instead of making progress with the democratic transition and the integration path, the various elements' interaction seems to place the region at risk of destabilisation and stalled progress coupled with the fact that not all requirements for stability have so far been met. The analysis concludes that the security framework is becoming increasingly complex and aggravated, in turn affecting the whole region's functioning and development and thus the entire Continent's stability and prosperity.
Keywords: Balkan Peninsula; Balkanski polotok; Democratization; Demokratizacija; European security; Evropska varnost; International security; Mednarodna varnost; Nation-building; Rekonstrukcija države